2020
DOI: 10.1080/13506285.2020.1797968
|View full text |Cite
|
Sign up to set email alerts
|

Atypically heterogeneous vertical first fixations to faces in a case series of people with developmental prosopagnosia

Abstract: When people recognise faces, they normally move their eyes so that their first fixation is in the optimal location for efficient perceptual processing. This location is found just below the centrepoint between the eyes. This type of attentional bias could be partly innate, but also an inevitable developmental process that aids our ability to recognise faces. We investigated whether a group of people with developmental prosopagnosia would also demonstrate neurotypical first fixation locations when recognising f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 70 publications
0
12
0
Order By: Relevance
“…Thus atypicalities in the WLE in prosopagnosia may support this expertise hypothesis. Burns, Tree, Chan, & Xu, 2017;Bate et al, 2019;Childs et al, 2021), and is commonly used to diagnose DP (Bate et al, 2014;Bate & Tree, 2016;Biotti & Cook, 2016;Biotti, Gray, & Cook, 2017;Burns, Martin, Chan, & Xu, 2017;Burns, Tree, & Weidemann, 2014;Wilcockson, Burns, Xia, Tree, & Crawford, 2020). Using norms from the original CFMT paper (Duchaine & Nakayama, 2006) and one-tailed Crawford's single case ttests (Crawford & Howell, 1998), we confirmed all 28 DP cases were abnormally impaired in face memory ability.…”
Section: Participants and Faces Tasksmentioning
confidence: 52%
“…Thus atypicalities in the WLE in prosopagnosia may support this expertise hypothesis. Burns, Tree, Chan, & Xu, 2017;Bate et al, 2019;Childs et al, 2021), and is commonly used to diagnose DP (Bate et al, 2014;Bate & Tree, 2016;Biotti & Cook, 2016;Biotti, Gray, & Cook, 2017;Burns, Martin, Chan, & Xu, 2017;Burns, Tree, & Weidemann, 2014;Wilcockson, Burns, Xia, Tree, & Crawford, 2020). Using norms from the original CFMT paper (Duchaine & Nakayama, 2006) and one-tailed Crawford's single case ttests (Crawford & Howell, 1998), we confirmed all 28 DP cases were abnormally impaired in face memory ability.…”
Section: Participants and Faces Tasksmentioning
confidence: 52%
“…Low power is not just an issue when researchers are using a single test, such as the CFMT, to diagnose prosopagnosia. Many authors require significant impairments at the single-case level on two (e.g., CFMT and FFT, Fisher et al, 2020 ; Pertzov et al, 2020 ; Stumps et al, 2020 ; Wilcockson et al, 2020 ) and sometimes three (CFMT, CFPT and a prosopagnosia questionnaire, Mishra et al, 2020 ) measures before they will confirm a diagnosis. We know that roughly 50% of potential DP cases will fail to meet diagnostic criteria when assessed using the CFMT (Bate et al, 2019a ; Burns et al, 2014a ; Murray & Bate, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…If researchers need impairment on one specific task (e.g., the CFMT: Gerlach et al, 2020 ), then they will be able to include 50% of potential DP cases in their studies, as on average, 50% of participants are sufficiently impaired at the single-case level to attain a diagnosis via the CFMT. However, if researchers need impairment on two specific tasks (e.g., the CFMT and FFT, Stumps et al, 2020 ; Wilcockson et al, 2020 ), or three (e.g., Fry et al, 2020 ), then these authors will test a much smaller sample of the most severely impaired cases who can meet all these criteria.…”
Section: Introductionmentioning
confidence: 99%
“…For example, many lab-based studies have found associations between face-processing ability and face information sampling patterns (e.g. 4,[66][67][68][69][70][71] for a review see 72 ). Relatedly, developmental disorders have been associated with abonomal social attention in laboratory-based studies (e.g.…”
Section: Discussionmentioning
confidence: 99%